Hepatic Campylobacter jejuni infection in patients with Castleman‐Kojima disease (idiopathic multicentric Castleman disease with thrombocytopenia, anasarca, fever, reticulin fibrosis, and organomegaly (TAFRO) syndrome). Issue 10 (20th October 2019) - Kageyama, Chihiro; Igawa, Takuro; Gion, Yuka; Iwaki, Noriko; Tabata, Tetsuya; Tanaka, Takehiro; Kondo, Eisei; Sakai, Hajime; Tsuneyama, Koichi; Nomoto, Kazuhiro; Noguchi, Hiroko; Yoshino, Tadashi; et al.
Abstract : Castleman‐Kojima disease, also known as idiopathic multicentric Castleman disease with TAFRO syndrome (iMCD‐TAFRO), is a recently recognized systemic inflammatory disorder with a characteristic series of clinical symptoms, including thrombocytopenia (T), anasarca (A), fever (F), reticulin fibrosis (R), and organomegaly (O). Patients with iMCD‐TAFRO often develop severe abdominal pain, elevated alkaline phosphatase levels, and systemic inflammation, but the etiological factors are unknown. To investigate the potential role of bacterial infection in the pathogenesis of iMCD‐TAFRO, we performed polymerase chain reaction (PCR) for the bacterial 16S rRNA gene with DNA extracted from liver specimens of three patients with iMCD‐TAFRO, four patients with amyotrophic lateral sclerosis, and seven patients with inflammatory conditions. Sequencing of the PCR product showed 99% DNA sequence identity with Campylobacter jejuni in all three patients with iMCD‐TAFRO and in two patients with inflammatory conditions. Immunohistochemical and electron microscopy analyses could not identify C. jejuni in patients with iMCD‐TAFRO. The findings indicated that C. jejuni infection is not the pathological cause of iMCD‐TAFRO; however, this ubiquitous bacterium may play a role in uncontrolled systemic hypercytokinemia, possibly through the development of cross‐reactive autoantibodies.